Billiards-inspired optimization algorithm; a new meta-heuristic method. (October 2020) - Kaveh, A.; Khanzadi, M.; Rastegar Moghaddam, M.
Abstract: This paper introduces a new physics-based meta-heuristic algorithm called Billiards-inspired Optimization Algorithm (BOA). The optimization process of this algorithm resembles the billiards game. Each solution candidate is considered as a multi-dimensional billiards ball and the best obtained solutions as pockets. When the balls encounter other balls, vector algebra and conservation laws determine final positions of the balls in optimization search space. In order to evaluate the validity of the proposed approach, twenty-three mathematical functions and seven constrained engineering benchmark problems are studied. The results indicated that the BOA can play an effective role in the field of optimization.